A mouse model for ulcerative colitis based on NOD-scid IL2R γnull mice reconstituted with peripheral blood mononuclear cells from affected individuals - Pia Palamides; Henrika Jodeleit; Michael Föhlinger; Florian Beigel; Nadja Herbach; Thomas Mueller; Eckhard Wolf; Matthias Siebeck; Roswitha Gropp (The Company of Biologists, 2016)
Animal models reflective of ulcerative colitis (UC) remain a major challenge, and yet are crucial to understand mechanisms underlying the onset of disease and inflammatory characteristics of relapses and remission. Mouse models in which colitis-like symptoms are induced through challenge with toxins such as oxazolone, dextran sodium sulfate (DSS) or 2,4,6-trinitrobenzenesulfonic acid (TNBS) have been instrumental in understanding the inflammatory processes of UC. However, these neither reflect the heterogeneous symptoms observed in the UC-affected population nor can they be used to test the efficacy of inhibitors developed against human targets where high sequence and structural similarity of the respective ligands is lacking. In an attempt to overcome these problems, we have developed a mouse model that relies on NOD-scid IL2R γnull mice reconstituted with peripheral blood mononuclear cells derived from UC-affected individuals. Upon challenge with ethanol, mice developed colitis-like symptoms and changes in the colon architecture, characterized by influx of inflammatory cells, edema, crypt loss, crypt abscesses and epithelial hyperplasia, as previously observed in immune-competent mice. TARC, TGFβ1 and HGF expression increased in distal parts of the colon. Analysis of human leucocytes isolated from mouse spleen revealed an increase in frequencies of CD1a+, CD64+, CD163+ and TSLPR+ CD14+ monocytes, and antigen-experienced CD44+ CD4+ and CD8+ T-cells in response to ethanol. Analysis of human leucocytes from the colon of challenged mice identified CD14+ monocytes and CD11b+ monocytes as the predominant populations. Quantitative real-time PCR (RT-PCR) analysis from distal parts of the colon indicated that IFNγ might be one of the cytokines driving inflammation. Treatment with infliximab ameliorated symptoms and pathological manifestations, whereas pitrakinra had no therapeutic benefit. Thus, this model is partially reflective of the human disease and might help to increase the translation of animal and clinical studies.